2018
DOI: 10.1016/j.drugalcdep.2018.06.018
|View full text |Cite|
|
Sign up to set email alerts
|

Longitudinal associations between youth tobacco and substance use in waves 1 and 2 of the Population Assessment of Tobacco and Health (PATH) Study

Abstract: Tobacco and substance use prevention efforts may benefit from comprehensive screening and interventions across tobacco products, alcohol, and drugs, and targeting risk factors shared across substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…Taken together, these findings indicate that adolescents who engage in early onset of e-cigarette use (ecigarette use only or dual use) should be assessed for substance-related problems based on their increased risk for polysubstance use. 29 Moreover, the findings of the present study indicate that prospective studies examining the association between e-cigarette use and cigarette smoking must adequately account for prior history of substance use behaviors, especially among older adolescents.…”
Section: Discussionmentioning
confidence: 74%
“…Taken together, these findings indicate that adolescents who engage in early onset of e-cigarette use (ecigarette use only or dual use) should be assessed for substance-related problems based on their increased risk for polysubstance use. 29 Moreover, the findings of the present study indicate that prospective studies examining the association between e-cigarette use and cigarette smoking must adequately account for prior history of substance use behaviors, especially among older adolescents.…”
Section: Discussionmentioning
confidence: 74%
“…Other studies have shown that cigarette smoking predicts ever hookah initiation,29 hookah use and snus use each predict ever and P30D cigarette smoking initiation,30 and any non-cigarette tobacco product use predicts ever cigarette smoking initiation 14. Taken together, the association between previous tobacco use and initiation of a new product could be due to common liability and/or shared risk factors31 32 such as proclivity to engage in risky behaviours/sensation-seeking,33 receptivity/susceptibility to use tobacco,34 35 having friends who use tobacco,36 other substance use37 or household exposure to tobacco,38 which were not examined in this study. Findings could also be due to nicotine dependence since all tobacco products contain the addictive substance, although perhaps in different amounts 39.…”
Section: Discussionmentioning
confidence: 99%
“…The association between e-cigarettes and alcohol, previously observed in other studies ( Morean et al, 2016 ; Schlienz & Lee, 2018 ; Taylor et al, 2017 ), together with data on social media trends ( Camenga et al, 2018 ; Chu et al, 2018 ; Sampasa-Kanyinga & Hamilton, 2018 ), indicates that use of the former is now a social activity ( Pepper et al, 2017 ; Yule & Tinson, 2017 ). This is particularly concerning not only in light of potential feedback effects due to the previously discussed outsize effects of peer behaviour, but also because e-cigarette use has been shown to increase the risk of cigarette smoking ( Barnett et al, 2015 ; Bold et al, 2018 ; Hammond et al, 2017 ), which also often co-occurs with alcohol use in social situations ( Berg et al, 2018 ; Gubner, Thrul, Kelly, & Ramo, 2018 ; Silveira et al, 2018 ), adding an additional layer of risk. Concerningly, early initiation of cigarette and alcohol co-use may increase the likelihood of opioid use ( Arterberry et al, 2016 ), and the possibility that vaping may come to replace smoking in this role cannot yet be discounted.…”
Section: Discussionmentioning
confidence: 99%